Abnormal development of mouse embryoid bodies lacking p27Kip1 cell cycle regulator - Bryja, Vítezslav; Cajánek, Lukás; Pacherník, Jirí; Hall, Anita C; Horváth, Viktor; Dvorák, Petr; Hampl, Ales (Stem cells (Dayton, Ohio), 2005)
Cultures of three-dimensional aggregates of embryonic stem cells (ESCs) called embryoid bodies (EBs) provide a valuable system for analyzing molecular mechanisms that regulate differentiation of this unique cell type. Cyclin-dependent kinase inhibitor p27Kip1 (p27) becomes elevated during the differentiation of mouse ESCs (mESCs). In this study, various aspects of differentiation of EBs produced from normal and p27-deficient mESCs were analyzed to address the biological significance of this elevation. It was found that EBs lacking p27 grew significantly bigger, but this was not accompanied by detect-able abnormalities in the activities of cyclin-dependent kinases (CDKs). In most EB cells, downregulation of activating cyclins rather than upregulation of inhibiting p27 is probably responsible for lowering the activity of their CDKs. Abnormalities in the development of specific cell lineages were also observed in p27-deficient EBs. These included elimination of cells positive for cytokeratin endo-A (TROMA-I) and increased proliferation and formation of cavities originating from cells positive for Lewis-X. Our data also suggest that although two different pools of Lewis-X-expressing cells, cluster forming (ESC-like) and cavity forming (neural progenitors), normally exist in EBs, the absence of p27 leads to the enhancement of only the neural pool. No failure was found when the neurogenic capacity of p27-deficient mESCs was tested using various protein markers. Together, our data point to a dual role of p27 in mESCs, with one role being in the regulation of proliferation and the other role in establishing some other aspects of a differentiated phenotype.
Keywords: proteiny buněčného cyklu; inhibitor p27 cyklin-dependentní kinasy; down regulace; kmenové buňky; imunoprecipitace; neurony; Cell Cycle; Tumor Suppressor Proteins; Cyclin-Dependent Kinase Inhibitor p27; Flow Cytometry; Phenotype; Cell Survival; antigen Lewis X; fluorescenční mikroskopie; Down-Regulation; buněčná diferenciace; nádorové supresorové proteiny; Immunoprecipitation; Neurons; kultivované buňky; průtoková cytometrie; Cells, Cultured; Up-Regulation; Stem Cells; imunohistochemie; upregulace; embryo savčí; buněčný cyklus; Immunohistochemistry; Mice; Lewis X Antigen; Cell Proliferation; časové faktory; Cell Differentiation; Microscopy, Fluorescence; fenotyp; Animals; western blotting; Cell Cycle Proteins; Blotting, Western; Embryo, Mammalian; myši; proliferace buněk; viabilita buněk; Time Factors; zvířata